Guiding literacy growth: a school leadership reading intervention project - Mohd Puad, Mohd Hazwan; Vijaya Kumar, Stephanie Cross; Abdullah, Arnida; Bishen, Gurcharan Singh (Universiti Putra Malaysia Press, 2024)
This study aimed to assess the reading proficiency of the After-School Reading Intervention Project in international schools in Selangor. The study was conducted on 20 respondents from an international school in Selangor, using a quantitative research technique. Data were obtained using a questionnaire and the analysis report of the pre-test and post-test in reading proficiency before and after implementing the After-School Reading Intervention Project. The results showed that the students found the improvement project extremely practical and helpful in improving reading skills and proficiency. The After-School Reading Intervention Project significantly improved students' reading skills, especially pronunciation, fluency, and expression. Students showed greater interest and confidence in reading post-intervention, aided by increased parental support and engaging materials. The reading workshops proved effective, and students and parents acknowledged the program's positive impact on literacy development. The implications for students and educational stakeholders, as well as future research suggestions, are highlighted.